PENGARUH WORD OF MOUTH DAN INFLUENCER MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK AQUA DI KOTA MEDAN - Irvan Rolyesh Situmorang; Chelsya Chelsya; Tiffany Tiffany (Manajemen: Jurnal Ekonomi USI, 2025)
This research investigates how Word of Mouth and Influencer Marketing affect the purchase decisions of Aqua products in Medan City. Employing a quantitative method, data were gathered through surveys from 50 Aqua consumers. The analysis, conducted with SPSS version 26 using multiple linear regression, showed that Word of Mouth alone does not significantly influence purchase decisions, whereas Influencer Marketing has a significant impact. Together, these variables significantly affect consumers’ buying choices. The Adjusted R Square of 0.130 indicates that 13% of the variation in purchase decisions is explained by these factors, while the remaining 87% is attributed to other variables outside the scope of this study. The results underscore the crucial role of Influencer Marketing in influencing consumer behavior in today’s digital landscape